Protein Intake as a Risk Factor of Overweight/Obesity in 8– to 12–Year-Old Children. Issue 52 (December 2015) - del Mar Bibiloni, Maria; Tur, Josep A.; Morandi, Anita; Tommasi, Mara; Tomasselli, Francesca; Maffeis, Claudio
Abstract : Abstract: Several studies investigating the relationship between body mass index (BMI), waist circumference (WC), and/or body fat (BF) with macronutrient composition of the diet have suggested that dietary composition may play an important role to overweight/obesity in childhood, but its relation remains inconclusive. The aim was to assess the association between energy intake (EI) and macronutrient diet composition with overweight/obesity among children. Nonrandomized cohort study including 396 Italian children and preadolescents (9–13 years old), 200 overweight/obese and 196 normal-weight. The children's weight, height, WC, and food intake were measured. Reported EI was higher in overweight/obese than in nonoverweight children; however, after body weight was considered, the overweight/obese children had less EI than their leaner counterparts. Percentages of EI from proteins, SFA, MUFA and PUFA (in males), and dietary fiber (g/1000 kcal) were higher in the overweight/obese children than in the leaner ones. EI from carbohydrates and fats was lower in overweight/obese males and females, respectively. Positive correlations between BMI and waist-to-height ratio with EI from proteins were found in males ( r  = 0.296, P  < 0.01 and r  = 0.326, P  < 0.01; respectively) and females ( r  = 0.374, P  < 0.01 and r  = 0.405, P  < 0.01; respectively), but negative correlations with fats were found in females ( r  = −0.240, P  < 0.01 and r  = −0.188, P  < 0.05; respectively). Using binary logistic regression, the highest EI from proteins were associated with higher odds ratio for overweight/obesity, while the lowest EI from carbohydrates was associated with higher odds ratio for overweight/obesity in males. Reported EI of overweight/obese children was higher than nonoverweight peers. Overweight/obese children had higher intakes of proteins compared with nonoverweight ones. Overweight/obese males and females showed lower EI from carbohydrates and fats, respectively, than their leaner counterparts. Abstract : Supplemental Digital Content is available in the text